2008
DOI: 10.1002/ca.20711
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the iliolumbar vein with application to the anterior retroperitoneal approach to the lumbar spine: A cadaver study

Abstract: Objectives of this study include identification of lumbosacral venous variations, designation of a critical area of dissection for surgical exposure, and comparison between both male/female and right/left-sided anatomy. Attempts were made to provide anatomic nomenclature that accurately describes these structures. Thirty-eight iliolumbar venous systems in 20 cadavers (11 females/9 males) were dissected. Each system was identified as one of three patterns of variation: common venous trunk (combining ascending l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
4
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 12 publications
7
16
4
7
Order By: Relevance
“…They proposed that this was due to the larger size of the female pelvis (Sivakumar et al, ). Unruh et al () noted that the common trunk, when present, was longer in males (mean 1.5 cm) than females (mean 1.2 cm).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…They proposed that this was due to the larger size of the female pelvis (Sivakumar et al, ). Unruh et al () noted that the common trunk, when present, was longer in males (mean 1.5 cm) than females (mean 1.2 cm).…”
Section: Resultsmentioning
confidence: 97%
“…The patterns of insertion are variable and are not always symmetrical between left and right sides. Only two studies found significant gender differences in the origin of the ALV (Sivakumar et al, ; Unruh, et al, ). Sivakumar et al () reported a difference in the distance from the formation of the IVC to the origin of the ALV, with females having a mean distance of 4.2 cm and males 3.0 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically seen mid body of L5, occasionally the authors have noted the iliolumbar vein to cross the disc space. One cadaveric study (33) found that 5% of LLSVs ran superficial to the obturator nerve whereas 66.6% ran superficial to the LST. The common iliac and both iliac arteries frequently become tortuous with age, and thus have variable position , passing anterior in 70% of cases and posterior to the obturator nerve in 30% of cases in one cadaveric study (34).…”
Section: Discussionmentioning
confidence: 99%
“…While complications of AILF may be more numerous when compared with the posterior spine surgical procedures recent efforts by many surgeons have been aimed at avoiding complications and have yielded many articles regarding safer techniques and have revealed intra-abdominal improved surgical approach8,9,24). Consequently, ALIF is a less demanding and dangerous procedure.…”
Section: Discussionmentioning
confidence: 99%